Justifikasi Keperluan Penahanan Reman Menurut Perundangan Islam Dan Sivil: Justification of Necessity of Remand According to the Islamic and Civil Law - Abd Rahim, Fathin Shahirah; Yusof, Wafaa'; ismail, Nurbazla (Jurnal Fiqh, 2018)
Remand detention is an additional detention required to complete the investigation of criminal cases that cannot be resolved within twenty-four hours. Enforcement of remand detention under criminal law in Malaysia is enacted under section 117 of the Criminal Procedure Code (CPC). However, this provision is not provided under shariah criminal procedure in Malaysia which results in presumption arises that this procedure is not important. Ironically, the importance of remand detention as one of the investigation procedure of suspect in criminal cases has been discussed among Islamic jurists. Therefore, this paper aims to justify the importance of remand detention according to the Islamic and civil perspectives. This is a qualitative study, which applies the content analysis framework of a few Islamic books, academic materials and others. This paper discovers that temporary detention has been practiced since the time of the Messenger of Allah (PBUH) and it is permissible by majority of Islamic scholars, because such remand detention is not intended to punish, but rather to investigate and prevent the suspect from running away. In addition, it is also intended to prevent the suspect from manipulating evidences and disturbing other witnesses who can assist the investigation process.